Newcastle and Infectious Bronchitis Vaccine Reactions in Commercial Broilers - Gary D. Butcher; Richard D. Miles; Amir H. Nilipour (EDIS, 2003)
There is considerable confusion in the commercial broiler industry relating to vaccination with Newcastle (ND) and infectious bronchitis (IB) vaccines. Questions arise over route of vaccination, age at vaccination, doses of vaccine to administer per bird, mixing of ND and IB vaccines or other vaccines, vaccine reactions, use of live vaccines versus bacterins, strains or serotypes of virus to include, need for and timing of revaccination, and others. This document is VM132, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 10, 2002.